PROSES PERKEMBANGAN ISLAM DI NUSANTARA, TEORI MASUKNYA DAN PUSAT PENDIDIKAN ISLAM MASA AWAL DI ASIA TENGGARA - Kusnadi Kusnadi; Bahaking Rama; Muhammad Rusydi Rasyid (CV. ADIBA ASIHA AMIRA, 2022)
Since the arrival of Islam in this region, Islamic education has been practiced in the archipelago. Islamic education begins with interpersonal and collective interactions between preachers (educators) and their students. After the Muslim community was formed somewhere, they started to build educational centers. The mosque not only functions as a place of worship but also as a place of education. The mosque is the leading Islamic educational institution in Southeast Asia, side by side with the houses where the scholars or preachers live. Meunasah emerged as the forerunner of educational institutions in Aceh, then followed by dayah